Carotid artery plaques and intima medial thickness in familial hypercholesteraemic patients on long-term statin therapy: A case control study. (January 2017) - Bos, Sven; Duvekot, Martijne H.C.; ten Kate, Gert-Jan R.; Verhoeven, Adrie J.M.; Mulder, Monique T.; Schinkel, Arend F.L.; Nieman, Koen; Watts, Gerald F.; Sijbrands, Eric J.G.; Roeters van Lennep, Jeanine E.
Abstract: Background and aims: Statins reduce subclinical atherosclerosis and premature atherosclerotic cardiovascular disease (ASCVD) in patients with familial hypercholesterolemia (FH). However, some FH patients still develop ASCVD despite statin therapy. We compared subclinical atherosclerosis assessed by carotid plaque presence and intima media thickness (C-IMT), in long-term statin-treated FH patients and healthy controls. Furthermore, we analysed whether carotid ultrasonography findings associated with subclinical coronary atherosclerosis. Methods: We assessed the presence of carotid plaques and C-IMT in 221 asymptomatic heterozygous FH patients (48% men; 46 ± 15 years) on long-term (10.0 ± 7.8 years) statin treatment and 103 controls (32% men, 47 ± 16 years). Results: The frequency of carotid plaques and C-IMT did not differ significantly between the FH patients and controls (69 (31%) versus 24 (23%), p  = 0.1 and 0.58 ± 0.13 versus 0.58 ± 0.12 mm, p  = 0.9, respectively). In a subgroup of 49 FH patients who underwent cardiac computed tomography, coronary artery calcification correlated with carotid plaque presence (R = 0.47; p  = 0.001), but not with C-IMT (R = 0.20; p  = 0.2). Conclusions: Carotid plaques and C-IMT did not differ between long-term statin-treated heterozygous FH patients and healthy controls. This shows that long-term statin treatment in these FH patients reduces carotid atherosclerosis to a degree of a healthy population. These findings strongly suggests that sonography of the carotid arteries during follow-up of statin-treated FH patients has limited value. Highlights: Carotid plaque and intima media thickness does not differ between statin-treated heterozygous FH patients and controls. This suggests a normalization of atherosclerotic cardiovascular disease (ASCVD) risk in statin-treated FH. Carotid IMT is not associated with coronary calcification in heterozygous FH patients. Carotid plaques are associated with coronary calcification in heterozygous FH patients. These findings suggest that sonography of carotid arteries during follow-up of statin-treated FH patients has limited value.